2012
DOI: 10.1080/03079457.2012.656578
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for accurate and prompt molecular diagnosis of clades of highly pathogenic avian influenza H5N1 viruses emerging in Vietnam

Abstract: Forty-six chickens and 48 ducks were sampled from four Vietnamese poultry premises in 2009 infected with H5N1 highly pathogenic avian influenza (HPAI) clade 2.3.2 and 2.3.4 viruses, which also differed by cleavage site (CS) sequences in their haemagglutinin (HA) genes. All clinical specimens (n0282), namely tracheal and cloacal swabs plus feathers, were tested by five Eurasian reverse-transcriptase AI RealTime polymerase chain reaction (RRT-PCR) methods. Bayesian modelling showed similar high sensitivity for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 47 publications
(60 reference statements)
0
33
0
Order By: Relevance
“…Thirty-seven of 120 individual swab samples and 5 of 12 tissue pools (Technical Appendix) were confirmed positive for avian influenza virus by identification of the matrix (M) gene and H5 real-time reverse transcription PCR (rRT-PCR) as described ( 5 ). A highly pathogenic pathotype was confirmed by RT-PCR, then Sanger sequencing of the hemagglutinin (HA) gene as described ( 5 ).…”
Section: The Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-seven of 120 individual swab samples and 5 of 12 tissue pools (Technical Appendix) were confirmed positive for avian influenza virus by identification of the matrix (M) gene and H5 real-time reverse transcription PCR (rRT-PCR) as described ( 5 ). A highly pathogenic pathotype was confirmed by RT-PCR, then Sanger sequencing of the hemagglutinin (HA) gene as described ( 5 ).…”
Section: The Studymentioning
confidence: 99%
“…A highly pathogenic pathotype was confirmed by RT-PCR, then Sanger sequencing of the hemagglutinin (HA) gene as described ( 5 ). This process showed the polybasic cleavage site PLRERRRKR/GLF from multiple bird swab and tissue samples from each shed.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The possible diagnostic utility of such samples is also noteworthy. A subsequent investigation of H5N1 HPAI infected chickens and ducks in Vietnam showed feathers to increase the sensitivity of AIV RRT-PCR testing and successful virus isolation (Slomka and others 2012). RNA extracted from the 13 feather pools and 32 faecal samples in the present investigation were also tested by a M gene RRT-PCR test which included an internal positive control (Petrauskene and others 2010).…”
mentioning
confidence: 99%
“…Although some field studies have reported the use of feathers for diagnosis of HPAI infection, 19,20 most provide few details on the stage of growth or body location of the feathers used. To our knowledge, there are no studies that have examined in detail the relative diagnostic value of swabs and feathers from different body locations and of varying maturity in individual chickens and ducks.…”
Section: Introductionmentioning
confidence: 99%